2022
DOI: 10.3389/ijph.2021.1604223
|View full text |Cite
|
Sign up to set email alerts
|

Trust in Institutions and the COVID-19 Threat: A Cross-Sectional Study on the Public Perception of Official Recommendations and of Othering in Switzerland

Abstract: Objectives: To explore how perceived disease threat and trust in institutions relate to vaccination intent, perceived effectiveness of official recommendations, and to othering strategies.Methods: We conducted a cross-sectional survey of Swiss adults in July 2020. Outcome variables were vaccination intent, perceived effectiveness of official recommendations and othering strategies (labelling a given social group as responsible for the disease and distancing from it). Independent variables were perceived diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Finally, correlation analysis mainly supported past literature about conspiracy theory beliefs, which are generally supported more by the political right (Imhoff et al, 2022) and relate to the intake of fewer vaccine doses (e.g., van Mulukom et al, 2020). Women adhere to conspiracy theories more than men, as discovered in some other studies with large samples (Gilles et al, 2022;Imhoff et al, 2022, study 2;Popoli & Longus, 2021;Stanovich et al, 2016;van Mulukom et al, 2020;Wagner-Egger et al, 2022). Note that the reverse result (Freeman & Bentall, 2017;Krouwel et al, 2017;Lobato et al, 2014), and sometimes no differences were found (Darwin et al, 2011;Dyrendal & Hestad, 2021;Goertzel, 1994;Kuhn et al, 2021;Swami et al, 2012).…”
Section: Discussionmentioning
confidence: 80%
“…Finally, correlation analysis mainly supported past literature about conspiracy theory beliefs, which are generally supported more by the political right (Imhoff et al, 2022) and relate to the intake of fewer vaccine doses (e.g., van Mulukom et al, 2020). Women adhere to conspiracy theories more than men, as discovered in some other studies with large samples (Gilles et al, 2022;Imhoff et al, 2022, study 2;Popoli & Longus, 2021;Stanovich et al, 2016;van Mulukom et al, 2020;Wagner-Egger et al, 2022). Note that the reverse result (Freeman & Bentall, 2017;Krouwel et al, 2017;Lobato et al, 2014), and sometimes no differences were found (Darwin et al, 2011;Dyrendal & Hestad, 2021;Goertzel, 1994;Kuhn et al, 2021;Swami et al, 2012).…”
Section: Discussionmentioning
confidence: 80%
“…Gilles et al ( 33 ), on the other hand, discovered in a study in Switzerland that trust in public health institutions is directly associated with the success of SARS-CoV-2 vaccination process. To put it another way, the more citizens trust health organizations, the more likely they are to follow official vaccination and protection measures ( 33 ).…”
Section: Public Administration Quality Of Service and Citizen Emotion...mentioning
confidence: 99%
“…Gilles et al ( 33 ), on the other hand, discovered in a study in Switzerland that trust in public health institutions is directly associated with the success of SARS-CoV-2 vaccination process. To put it another way, the more citizens trust health organizations, the more likely they are to follow official vaccination and protection measures ( 33 ). Based on this evidence, institutional reform is required to place the citizen at the core of the State’s priorities in order to build a country with opportunities for all ( 12 ), as well as to allow the State to establish a national dialog with the private sector from a firm and consolidated position, supported by solid institutions ( 34 ).…”
Section: Public Administration Quality Of Service and Citizen Emotion...mentioning
confidence: 99%
“…Hence, there is a plea in favor of the development of more inclusive policies and frameworks in SARS-CoV-2 vaccine allocation for disadvantaged groups such as incarcerated people, homeless people, asylum seekers and undocumented migrants (Farina, Lavazza, 2021). Again, age and level of education are factors associated with the perception of o cial protective measures and vaccination intent (Gilles et al, 2022). Similar ndings on higher vaccination hesitancy among members of minority groups have been reported in other studies as well -Black Americans compared to White Americans, underlining the "wait-and-see" approach, vaccine side effects and e cacy, alongside other perceptions related to access and medical mistrust, against the background of systemic racism (Dong et al 2022).…”
Section: Research Background: Previous Research On Vaccine Hesitancymentioning
confidence: 99%